Délkelet-Európe korai állattartásának Hialakulása és közel-keleti kapisolatei - Bökönyi, S. (1977)
The Formation and the Near-Eastern Relations of Early Animal Husbandry in South-Eastern Europe; English summary 304f.; uses cuneiform economic texts.